Very late bioprosthetic aortic valve thrombosis. Issue 5 (8th May 2019) - Balakrishnan, Kuhendra; Herman, Brian; Koshy, George
Abstract : A 79-year-old man with a history of bioprosthetic aortic valve (AV) replacement in 2008 and atrial fibrillation was admitted with acute pulmonary oedema. Transthoracic and transoesophageal echocardiograms revealed significantly elevated AV gradients and thickened AV leaflets. These findings were suggestive of bioprosthetic valve thrombosis (BVT). The patient was treated with intravenous heparin and commenced on vitamin K antagonist. BVT remains an under recognised cause of late prosthetic valve dysfunction. A lack of awareness of BVT occurring beyond 3 months post-implantation is likely to account for this. Furthermore, structural valve degeneration is the most common mechanism of late prosthetic valve dysfunction. Recognising the difference between the two aetiologies is crucial as the management plan differs significantly. Here, we report a case of very late bioprosthetic AV thrombosis diagnosed 8 years after implantation. This was successfully treated with systemic anticoagulation, thereby avoiding the need for redo cardiac surgery.